Experimental Protocols and Analytical Procedures for Studying Synaptic Transmission in Rodent Spinal Cord Dorsal Horn. Issue 4 (18th April 2022) - Bardoni, Rita
Abstract: Synaptic modulation and plasticity are key mechanisms underlying pain transmission in the spinal cord and supra‐spinal centers. The study and understanding of these phenomena are fundamental to investigating both acute nociception and maladaptive changes occurring in chronic pain. This article describes experimental protocols and analytical methods utilized in electrophysiological studies to investigate synaptic modulation and plasticity at the first station of somatosensory processing, the spinal cord dorsal horn. Protocols useful for characterizing the nature of synaptic inputs, the site of modulation (pre‐ versus postsynaptic), and the presence of short‐term synaptic plasticity are presented. These methods can be employed to study the physiology of acute nociception, the pathological mechanisms of persistent inflammatory and neuropathic pain, and the pharmacology of receptors and channels involved in pain transmission. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Spinal cord dissection and acute slice preparation Basic Protocol 2 : Stimulation of the dorsal root and extracellular recording (compound action potentials and field potentials) Basic Protocol 3 : Patch‐clamp recording from dorsal horn neurons: action potential firing patterns and evoked synaptic inputs Basic Protocol 4 : Analysis of parameters responsible for changes in synaptic efficacy Basic Protocol 5 : Recording and analysis of currents mediated by astrocytic glutamate